Morphology of the First Zoeal Stage of the Shrimp Typton distinctus Chace, 1972: The Second for the Genus Typton O.G. Costa, 1844 After 100 Years - Sene, Matheus [UNESP]; Costa, Rogerio Caetano [UNESP]; Santos, Rafael Carvalho [UNESP] (Wiley, 2025)
ABSTRACT The marine shrimp of the genus Typton are widely distributed, known to be associated with sessile organisms such as sponges. Information about this genus is limited, highlighting the scarcity of important features in its biology, including larval forms. This study aims to describe the first larval stage of Typton distinctus , marking the third larval description for the genus and the second for the first zoea after 100 years. An ovigerous female was sampled manually by freediving in January 2019 at Cais do Porto, Itaguá Bay, Ubatuba, São Paulo. The parental female was kept in an aquarium until the larvae hatched. The morphology of the first larval stage was described and illustrated, then compared to the only first zoea of the genus available in the literature in this stage, T. spongicola , to identify diagnostic larval patterns in the genus. Both species shared similar morphological characteristics, typical of first zoea in caridean shrimp; however, an elevated number of distinct traits were identified too that could be a result of incomplete details in the description of T. spongicola . This study enhances the understanding of Typton larvae, assisting in their identification and providing information for future research on this genus through the morphological data provided.